2001
DOI: 10.1212/wnl.57.9.1679
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, incidence, and mortality of PD

Abstract: The prevalence and incidence rates of PD in Taiwan were much higher than those reported in China, but closer to those in Western countries. These results suggest that environmental factors may be more important than racial factors in the pathogenesis of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
144
5
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(166 citation statements)
references
References 36 publications
9
144
5
5
Order By: Relevance
“…Several studies reported lower prevalence of PD in Africa [21,40,[71][72][73], Asia [32,46,62,[65][66][67]74] and South America [63,64] compared to Europe [16,17,19,22,25,58,60,61,75]. To facilitate comparison among 25 studies conducted in different countries, Zhang et al [76] calculated age-standardized prevalence proportions using the US population in 1970 as the standard.…”
Section: Diagnosis Of Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported lower prevalence of PD in Africa [21,40,[71][72][73], Asia [32,46,62,[65][66][67]74] and South America [63,64] compared to Europe [16,17,19,22,25,58,60,61,75]. To facilitate comparison among 25 studies conducted in different countries, Zhang et al [76] calculated age-standardized prevalence proportions using the US population in 1970 as the standard.…”
Section: Diagnosis Of Pdmentioning
confidence: 99%
“…Studies performed after the late 1960s -when treatment with l-dopa was introduced -reporting mortality of patients with PD compared to that of persons without the disease are summarized in Table 3 [32,41,[87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102]. These studies quite consistently reported about a two-fold increased mortality rate among patients with PD than in the general population, although the range was between 1.3 and 5.7.…”
Section: Mortalitymentioning
confidence: 99%
“…MOHAMED SALAMA 1,2 , MAHMOUD SOBH 1 , MAHMOUD EMAM 1 , AHMED ABDALLA 1 , protein handling. PD is the second most common neurodegenerative disorder after Alzheimer's disease (3).…”
Section: Effect Of Intranasal Stem Cell Administration On the Nigrostmentioning
confidence: 99%
“…The reported incidence rates of PD vary largely. The lowest PD incidence was reported to be 4.5/1,000000 in Libya, while the highest incidence was reported in the USA at 20/1,000000 (1). The early symptoms of PD include slowness of movement, rigidity, shaking and walking difficulties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation